Academic Freedom in Latin America and the Deceptive Comfort of Autonomy - Bernasconi, Andrés (International Higher Education, 2024)
Universities in Latin America have long benefited from the explicit juridical protection of their autonomy. While overt attacks on university autonomy have been rare in recent decades, the right-wing Bolsonaro administration in Brazil, which seriously disturbed federal universities and funding agencies for science, illustrates a core weakness in the Latin American concept of autonomy: the secondary and subordinate position it gives to academic freedom.